Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Given the equation [tex]\( a + b + c = 0 \)[/tex], we aim to find the value of [tex]\( (a + b)(b + d(c + 1)) \)[/tex].
### Step-by-Step Solution:
1. Substituting values:
Let’s assume some values:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 2 \)[/tex]
2. Determining [tex]\( c \)[/tex]:
Since [tex]\( a + b + c = 0 \)[/tex], substituting the values we get:
[tex]\[ 1 + 2 + c = 0 \][/tex]
Solving for [tex]\( c \)[/tex], we have:
[tex]\[ 3 + c = 0 \][/tex]
[tex]\[ c = -3 \][/tex]
3. Assuming another variable [tex]\( d \)[/tex]:
Let [tex]\( d = 3 \)[/tex].
4. Evaluate [tex]\( a + b \)[/tex]:
[tex]\[ a + b = 1 + 2 = 3 \][/tex]
5. Evaluate [tex]\( c + 1 \)[/tex]:
[tex]\[ c + 1 = -3 + 1 = -2 \][/tex]
6. Evaluate [tex]\( d(c + 1) \)[/tex]:
[tex]\[ d(c + 1) = 3 \times (-2) = -6 \][/tex]
7. Evaluate [tex]\( b + d(c + 1) \)[/tex]:
[tex]\[ b + d(c + 1) = 2 + (-6) = 2 - 6 = -4 \][/tex]
8. Finally, calculate [tex]\( (a + b)(b + d(c + 1)) \)[/tex]:
[tex]\[ (a + b)(b + d(c + 1)) = 3 \times (-4) = -12 \][/tex]
### Recap of final values:
- [tex]\( a + b = 3 \)[/tex]
- [tex]\( b + d(c + 1) = -4 \)[/tex]
- The final result is:
[tex]\[ (a + b)(b + d(c + 1)) = -12 \][/tex]
Thus, the value of [tex]\( (a + b)(b + d(c + 1)) \)[/tex] is [tex]\(-12\)[/tex].
### Step-by-Step Solution:
1. Substituting values:
Let’s assume some values:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 2 \)[/tex]
2. Determining [tex]\( c \)[/tex]:
Since [tex]\( a + b + c = 0 \)[/tex], substituting the values we get:
[tex]\[ 1 + 2 + c = 0 \][/tex]
Solving for [tex]\( c \)[/tex], we have:
[tex]\[ 3 + c = 0 \][/tex]
[tex]\[ c = -3 \][/tex]
3. Assuming another variable [tex]\( d \)[/tex]:
Let [tex]\( d = 3 \)[/tex].
4. Evaluate [tex]\( a + b \)[/tex]:
[tex]\[ a + b = 1 + 2 = 3 \][/tex]
5. Evaluate [tex]\( c + 1 \)[/tex]:
[tex]\[ c + 1 = -3 + 1 = -2 \][/tex]
6. Evaluate [tex]\( d(c + 1) \)[/tex]:
[tex]\[ d(c + 1) = 3 \times (-2) = -6 \][/tex]
7. Evaluate [tex]\( b + d(c + 1) \)[/tex]:
[tex]\[ b + d(c + 1) = 2 + (-6) = 2 - 6 = -4 \][/tex]
8. Finally, calculate [tex]\( (a + b)(b + d(c + 1)) \)[/tex]:
[tex]\[ (a + b)(b + d(c + 1)) = 3 \times (-4) = -12 \][/tex]
### Recap of final values:
- [tex]\( a + b = 3 \)[/tex]
- [tex]\( b + d(c + 1) = -4 \)[/tex]
- The final result is:
[tex]\[ (a + b)(b + d(c + 1)) = -12 \][/tex]
Thus, the value of [tex]\( (a + b)(b + d(c + 1)) \)[/tex] is [tex]\(-12\)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.